2008
DOI: 10.1017/s0954579408000394
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions and school readiness intervention: Impact, moderation, and mediation in the Head Start REDI program

Abstract: Despite their potentially central role in fostering school readiness, executive function (EF) skills have received little explicit attention in the design and evaluation of school readiness interventions for socioeconomically disadvantaged children. The present study examined a set of five EF measures in the context of a randomized-controlled trial of a research-based intervention integrated into Head Start programs (Head Start REDI). Three hundred fifty-six 4-year-old children (17% Hispanic, 25% African Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
485
1
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 617 publications
(526 citation statements)
references
References 75 publications
26
485
1
14
Order By: Relevance
“…Children receiving these interventions have demonstrated more socially competent behavior (Domitrovich et al 2007) and significant improvements in self-regulation (Bierman et al 2008b) compared to children in a control group. Another recent study examining a broad intervention targeting social-emotional learning and literacy development found that children in intervention schools demonstrated improvements in a variety of social behaviors and self-regulation skills (e.g., attention).…”
Section: Integrating Levels Of Influence In Self-regulation Interventmentioning
confidence: 99%
“…Children receiving these interventions have demonstrated more socially competent behavior (Domitrovich et al 2007) and significant improvements in self-regulation (Bierman et al 2008b) compared to children in a control group. Another recent study examining a broad intervention targeting social-emotional learning and literacy development found that children in intervention schools demonstrated improvements in a variety of social behaviors and self-regulation skills (e.g., attention).…”
Section: Integrating Levels Of Influence In Self-regulation Interventmentioning
confidence: 99%
“…Regarding mental health problems, SEL programs proved efficient in reducing depression (Lewis et al, 2013;Schonert-Reichl et al, 2015), general anxiety (Bavarian et al, 2013), social anxiety (Coelho, Marchante, & Sousa, 2015) and other emotional problems (Humphrey, Kalambouka, Wigelsworth, & Lendrum, 2010;Muratori et al, 2015). Also, other studies reported an increase in social and emotional competencies (Bierman, Nix, Greenberg, Blair, & Domitrovich, 2008;Caldarella, Christensen, Kramer, & Kronmiller, 2009;Castillo, Salguero, Fernandez-Berrocal, & Balluerka, 2013;Pendry, Carr, Smith, & Roeter, 2014). Moreover, social and emotional learning programs have shown positive results in increasing academic performance in youth (Bradley, Galvin, Atkinson, & Tomasino, 2012;Bavarian et al, 2013).…”
Section: Social Emotional Learningmentioning
confidence: 92%
“…In order to be successful in the classroom, children also need to develop strong learning skills and remain engaged in the classroom if they are to fully benefit from instruction and learning experiences (Bierman et al, 2008;Fredricks, Blumenfeld & Paris, 2004). Recently, the importance of engagement reflecting commitment and persistence toward learning and academic goals has received attention as a promising target for interventions aimed at reducing student dropout and poor academic achievement (Fredricks et al, 2004;Janosz, Archambault, Morizot & Pagani, 2008).…”
Section: The Importance Of School Readinessmentioning
confidence: 99%
“…Few programmes, to date, have been designed to specifically improve cognitive control and classroom engagement in pre-school aged children. Nonetheless, Tools of the Mind pre-school programme (Bodrova & Leong, 2007), Montessori Education (Lillard & Else-Quest, 2006), and the REDI programme (Bierman, Domitrovich et al, 2008;Bierman, Nix, Greenberg, Blair & Domitrovich, 2008) have been designed to improve child cognitive control and classroom learning behaviour. Other programmes have included child self-regulation components within larger objectives (e.g.…”
Section: Implications Curriculum and Classroom Engagementmentioning
confidence: 99%
See 1 more Smart Citation